Modelo de contribuições de grupos aplicado a reações para a formação do biodiesel - Oliveira, Amanda Cristina de (Universidade Federal de São Carlos, 2010)
The interest in biofuels has increased substantially in recent years due, mainly, to reduced damage to the environment compared to conventional fuels derived from petroleum. Accordingly, biodiesel has been studied by researchers around the world. The main routes of production of biodiesel are the reactions of esterification of fatty acids and transesterification of triacylglycerides. The reagents most commonly used are the short-chain alcohols such as methanol, ethanol, propanol and butanol. In Brazil, the study of those reactions by ethanol has been emphasized, since the country is the second largest producer of ethanol. Therefore, researches related to biodiesel production are important. This study has developed a method of group contribution to estimate enthalpies of formation and absolute entropies, both at standard state and liquid phase. This method has aimed to estimate those two thermodynamic properties for chemical species involved in the reactions of biodiesel formation. With those estimates and the use of the UNIFAC method, it was possible to predict the chemical equilibrium of esterification reactions. The estimate of the properties by the method of contribution group was tested for 59 chemical species, in the case of enthalpy of formation and to 15 for the absolute entropy. The results were compared with literature data and the relative deviations found for the enthalpy and entropy showed values of - 0.3 % and 0.4 % respectively. The method was accurate to estimate triacylglycerides, such as triolein and glyceryl triacetate. Thus, the molar fractions in the equilibrium of esterification reactions were estimated and compared with experimental data, with arithmetic mean of the relative deviations of -2.32 %. With those results, the simulations of reactions of esterification of saturated and unsaturated fatty acids were possible. Moreover, during the development of the method of group contribution, equations were derived and used to correct the shortcomings of the literature concerning with absolute entropies of gases and liquids.
Keywords: Engenharia química; Biodiesel; Equilíbrio químico; Termodinâmica; Esterificação; Biodiesel; Contribuições de grupos; Esterificação; Biodiesel; Group contribution; Chemical equilibrium; Thermodynamics; Esterification; ENGENHARIAS::ENGENHARIA QUIMICA